Designing Implementation and Application of KRS Filling Using the Web (Case Study at the University): Designing Implementation and Application of KRS Filling Using the Web (Case Study at the University) - Yohana Mastarida Manurung; Fauziah Fauziah; Novi Dian Natasia (Jurnal Mantik, 2020)
The development of technology is now very rapidly developing and making new breakthroughs and the increasing need for good information systems to encourage us to do all activities can run properly and we are encouraged to make a right decision and so that we can get a progress on the information system. One of the tertiary institutions also really needs an information system to make it easier for students to fill KRS and reduce errors and be able to collect data quickly. KRS system is needed and makes it very easy for students to fill KRS and increase student satisfaction with the system. Nowadays many universities have implemented KRS filling systems online. The method used is SLDC (System Development Life Cycle) and object-oriented development starting from analyzing a system that runs through UML (Unified Modelung Language). With the programming language used is PHP and the database used MySQL. The design of the higher education system produces computerized information technology benefits so as to minimize the filling of KRS online. In addition, it can produce application designs that can improve the operational performance of higher education. The design of the higher education system produces computerized information technology benefits so as to minimize the filling of KRS online. In addition, it can produce application designs that can improve the operational performance of higher education. The design of the higher education system produces computerized information technology benefits so as to minimize the filling of KRS online. In addition, it can produce application designs that can improve the operational performance of higher education.